Molecular cytogenetic analysis of the wheat-Agropyron elongatum partial amphiploid BE-1 - Sepsi, Adél (Acta Biologica Szegediensis, 2008)
Multicolor genomic in situ hybridization (mcGISH) and fluorescence in situ hybridization (FISH) using repetitive DNA probes were used to characterize the genomic composition of the wheat-Thinopyrum ponticum partial amphiploid BE-1. The amphiploid is a high-protein line having resistance to leaf rust (Puccinia recondita f. sp. tritici) and powdery mildew (Blumeria graminis f. sp. tritici) and has in total 56 chromosomes per cell. Multicolor GISH revealed 16 chromosomes originating from Thinopyrum ponticum and 14 A genome, 14 B genome and 12 D genome chromosomes. Rearrangements involving Thinopyrum chromosomes and the A, B and D genomes of wheat were visualised. FISH using repetitive DNA probes allowed the identification of all wheat chromosomes present and the determination of the chromosomes involved in translocations.